Development of digital instrumentation for bond rupture detection : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Palmerston North, New Zealand - Van der Werff, Matthew John (Massey University, 2009)
In the medical world the precise identification of a disease can take longer than it is safe to wait to start treatment so there is a need for faster and more precise biosensors. Bond Rupture is a new sensor technique that maybe able to improve disease detection. It does this by inducing bonds to rupture from the surface, and also measuring the point at which this rupture occurs this enables the forces to be measured on the surface. Specifically, this project has focused on the application of Bond Rupture to detecting antigens when bound to a surface using their specific antibodies, and the idea that the rupture force of these antigens can also be measured. The sensor that this project is based around is the Quartz Crystal Microbalance (QCM), which oscillates horizontally when a voltage is applied, and can also be used to measure mass change on its surface via change in resonant frequency. The aim of this project was to investigate possible Bond Rupture detection methods and techniques and has involved the development of a high speed digital electronics system, for the purposes of inducing and detecting Bond Rupture. This has involved the development of a FPGA based high speed transceiver board which is controlled by a Digital Signal Processor (DSP), as well as the development of various graphical user interfaces for end user interaction. Bond rupture testing was carried out by rupturing beads from the surface of a QCM in an experiment taking as little as 20 seconds. The Bond Rupture effect has been observed via the high accuracy measurement of the frequency change while inducing Bond Rupture on the sensor, proving that the Bond Rupture effect indeed exists. The research performed is believed to be a world first in terms of the method used and accuracy acquired.
Keywords: Biosensors; Quartz Crystal Microbalance (QCM)